Multiparametric High‐Content Assays to Measure Cell Health and Oxidative Damage as a Model for Drug‐Induced Liver Injury. Issue 4 (14th December 2020) - Pohan, Grace; Espinosa, Jether Amos; Chen, Steven; Ang, Kenny K.; Arkin, Michelle R.; Markossian, Sarine
Abstract: Drug‐induced liver injury is an important cause of non‐approval in drug development and the withdrawal of already approved drugs from the market. Screening human hepatic cell lines for toxicity has been used extensively to predict drug‐induced liver injury in preclinical drug development. Assessing hepatic‐cell health with more diverse markers will increase the value of in vitro assays and help predict the mechanism of toxicity. We describe three live cell‐based assays using HepG2 cells to measure cell health parameters indicative of hepatotoxicity. The first assay measures cellular ATP levels using luciferase. The second and third assays are multiparametric high‐content screens covering a panel of cell health markers including cell count, mitochondrial membrane potential and structure, nuclear morphology, vacuolar density, and reactive oxygen species and glutathione levels. © 2020 Wiley Periodicals LLC. Basic Protocol 1 : Measurement of cellular ATP content Basic Protocol 2 : High‐content analysis assay to assess cell count, mitochondrial membrane potential and structure, and reactive oxygen species Basic Protocol 3 : High‐content analysis assay to assess nuclear morphology, vacuoles, and glutathione content Support Protocol 1 : Subculturing and maintaining HepG2 cells Support Protocol 2 : Plating HepG2 cell line Support Protocol 3 : Transferring compounds by pin tool Support Protocol 4 : Generating dose‐response curves